A multicenter study of plasma use in the United States. Issue 6 (19th December 2014) - Triulzi, Darrell; Gottschall, Jerome; Murphy, Edward; Wu, Yanyun; Ness, Paul; Kor, Daryl; Roubinian, Nareg; Fleischmann, Debra; Chowdhury, Dhuly; Brambilla, Donald; NHLBI Recipient Epidemiology; Donor Evaluation Study‐III (REDS‐III)
<x xml:space="preserve">Abstract</x> Background Detailed information regarding plasma use in the United States is needed to identify opportunities for practice improvement and design of clinical trials of plasma therapy. Study Design and Methods Ten US hospitals collected detailed medical information from the electronic health records for 1 year (2010‐2011) for all adult patients transfused with plasma. Results A total of 72, 167 units of plasma were transfused in 19, 596 doses to 9269 patients. The median dose of plasma was 2 units (interquartile range, 2‐4; range 1‐72); 15% of doses were 1 unit, and 45% were 2 units. When adjusted by patient body weight (kg), the median dose was 7.3 mL/kg (interquartile range, 5.5‐12.0). The median pretransfusion international normalized ratio (INR) was 1.9 (25%‐75% interquartile range, 1.6‐2.6). A total of 22.5% of plasma transfusions were given to patients with an INR of less than 1.6 and 48.5% for an INR of 2.0 or more. The median posttransfusion INR was 1.6 (interquartile range, 1.4‐2.0). Only 42% of plasma transfusions resulted in a posttransfusion INR of less than 1.6. Correction of INR increased as the plasma dose increased from 1 to 4 units (p < 0.001). There was no difference in the INR response to different types of plasma. The most common issue locations were general ward (38%) and intensive care unit (ICU; 42%). Conclusion This large database describing plasma utilization in the United States provides evidence for both inadequate dosing and unnecessary transfusion. Measures to improve plasma transfusion practice and clinical trials should be directed at patients on medical and surgical wards and in the ICU where plasma is most commonly used.